A NORMAL BRADYSYSTOLIC FORM OF ATRIAL FIBRILLATION (FREDERICQ’S SYNDROME): LATE DIAGNOSIS AND TREATMENT - N. Ye. Trekina; A. V. Rudenko; I. A. Urvantseva; L. V. Salamatina; Ye. V. Korneeva (Klinicist, 2014)
It is presented a case of delayed diagnosis brad systole against permanent atrial fibrillation (syndrome Frederick) which became to syncope patient and to the later implanting of pacemaker.